Housing improvements and Malaria risk in Sub-Saharan Africa: A multi-country analysis of survey data - Tusting, L; Gibson, H; Gething, P; Bottomley, C; Kleinschmidt, I; Tatem, A; Lindsay, S (Public Library of Science, 2017)
Background Improvements to housing may contribute to malaria control and elimination by reducing house entry by malaria vectors and thus exposure to biting. We tested the hypothesis that the odds of malaria infection are lower in modern, improved housing compared to traditional housing in sub-Saharan Africa (SSA). Methods and Findings Fifteen Demographic and Heath Surveys (DHS) and 14 Malaria Indicator Surveys (MIS) conducted in 21 countries in SSA between 2008 and 2015, that measured malaria infection by microscopy or rapid diagnostic test (RDT), were analysed. DHS/MIS surveys record whether houses are built with finished materials (e.g. metal) or rudimentary materials (e.g. thatch). This information was used to develop a binary housing quality variable where houses built using a finished wall, roof and floor material were classified as ‘modern’ and all other houses were classified as ‘traditional’. Conditional logistic regression was used to determine the association between housing quality and prevalence of malaria infection in children aged 0-5 years, adjusting for age, gender, insecticide-treated net (ITN) use, indoor residual spraying, household wealth and geographic cluster. Individual survey odds ratios (OR) were combined to determine a summary OR using a random effects meta-analysis. Of 284,532 total children surveyed, 139,318 were tested for malaria infection using microscopy (n= 131,652) or RDT (n= 138,540). Modern housing was associated with a 9% to 14% reduction in the odds of malaria infection (microscopy: adjusted OR 0.91, 95% confidence intervals (CI) 0.85-0.97, p=0.003; RDT: adjusted OR 0.86, 95% CI 0.80-0.92, p<0.001). This effect was consistent regardless of ITN usage. As a comparison, the odds of malaria infection were 15% to 16% lower among ITN users, versus non-users (microscopy: adjusted OR 0.84, 95% CI 0.79-0.90, p<0.001; RDT: adjusted OR 0.85, 95% CI 0.80-0.90, p<0.001). The main limitation of this study is that residual confounding by household wealth of the effects of housing quality and ITNs is possible, since the wealth index may not have fully captured differences in socioeconomic position; however, the use of multiple national surveys offers the advantage of a large sample size and the elimination of many biases typically associated with pooling observational data. Conclusions Housing quality is an important risk factor for malaria infection across the spectrum of malaria endemicity in SSA, with a similar magnitude of effect to ITNs. Improved housing should be considered a promising intervention for malaria control, elimination and long-term prevention of reintroduction.